Accentuated eccentric loading for training and performance: A review - Wagle, J. P.; Taber, C. B.; Cunanan, A. J.; Bingham, G. E.; Carroll, K. M.; DeWeese, B. H.; Sato, K.; Stone, M. H. (Sports Medicine, 2017)
Accentuated eccentric loading (AEL) prescribes eccentric load magnitude in excess of the concentric prescription using movements that require coupled eccentric and concentric actions, with minimal interruption to natural mechanics. This method has been theorized to potentiate concentric performance through higher eccentric loading and, thus, higher concentric force production. There is also evidence for favorable chronic adaptations, namely shifts to faster myosin heavy chain isoforms and changes in IIx-specific muscle cross-sectional area. However, research concerning the acute and chronic responses to AEL is inconclusive, likely due to inconsistencies in subjects, exercise selection, load prescription, and method of providing AEL. Therefore, the purpose of this review is to summarize: (1) the magnitudes and methods of AEL application; (2) the acute and chronic implications of AEL as a means to enhance force production; (3) the potential mechanisms by which AEL enhances acute and chronic performance; and (4) the limitations of current research and the potential for future study.